Assessment of Ascorbic Acid and Heavy Metal Contamination in Mango Mangifera indica Varieties from Southern Libya: Implications for Food Safety and Nutritional Quality (Libyan Journal of Ecological & Environmental Sciences and Technology, 2025)
This study provides a comprehensive evaluation of ascorbic acid (vitamin C) content and selected heavy metals (Fe, Cu, Zn, Pb) in mango (Mangifera indica L.) varieties cultivated in southern Libya. Samples were collected from seven agricultural regions and analyzed using Atomic Absorption Spectroscopy (AAS) and iodometric titration. The mean concentrations (±SD) of Fe, Cu, Zn, and Pb in mango pulp and peel were found to be within WHO permissible limits, confirming their safety for consumption. Vitamin C levels ranged from 11.44 ± 0.5 mg/g to 55.44 ± 0.9 mg/g, indicating strong antioxidant potential. These findings suggest that mango fruits grown in southern Libya are nutritionally rich and environmentally safe. The study provides baseline data for environmental monitoring, agricultural sustainability, and public health protection.
Keywords: Heavy metals; Ascorbic acid; Mango; Food safety; Southern Libya